Geomatic methods applied to the change study of the la Paúl Rock Glacier, Spanish Pyrenees - Martínez Fernández, Adrián; Serrano Cañadas, Enrique; Sanjosé Blasco, José Juan de; Gómez Lende, Manuel; Pisabarro Pérez, Alfonso; Sánchez, M. (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Producción Científica Rock glaciers are one of the most important features of the mountain permafrost in the Pyrenees. La Paúl is an active rock glacier located in the north face of the Posets massif in the La Paúl glacier cirque (Spanish Pyrenees). This study presents the preliminary results of the La Paúl rock glacier monitoring works carried out through two geomatic technologies since 2013: Global Navigation Satellite System (GNSS) receivers and Terrestrial Laser Scanning (TLS) devices. Displacements measured on the rock glacier surface have demonstrated both the activity of the rock glacier and the utility of this equipment for the rock glaciers dynamic analysis. The glacier has exhibited the fastest displacements on its west side (over 35 cm yr-1), affected by the Little Ice Age, and frontal area (over 25 cm yr-1). As an indicator of permafrost in marginal environments and its peculiar morphology, La Paúl rock glacier encourages a more prolonged study and to the application of more geomatic techniques for its detailed analysis. Ministerio de Economía, Industria y Competitividad - Fondo Europeo de Desarrollo Regional (project CGL2015-68144-R) Junta de Extremadura - Fondo Europeo de Desarrollo Regional (project GR10071)